2014
DOI: 10.1103/physrevb.90.094403
|View full text |Cite
|
Sign up to set email alerts
|

Observation of inverse spin Hall effect in bismuth selenide

Abstract: ) is a topological insulator exhibiting helical spin polarization and strong spin-orbit coupling. The spin-orbit coupling links the charge current to spin current via the spin Hall effect (SHE). We demonstrate a Bi 2 Se 3 spin detector by injecting the pure spin current from a magnetic permalloy layer to a Bi 2 Se 3 thin film and detect the inverse SHE in Bi 2 Se 3 . The spin Hall angle of Bi 2 Se 3 is found to be 0.0093 ± 0.0013 and the spin diffusion length in Bi 2 Se 3 to be 6.2 ± 0.15 nm at room temperatur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
155
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(180 citation statements)
references
References 53 publications
(78 reference statements)
20
155
0
Order By: Relevance
“…Distinguished from ordinary insulators by the so-called Z 2 topological invariants associated with the bulk electronic band structure [2,3], this class of materials is characterized by nonlocal topology of the electronic structure that gives rise to new electronic states with promise for realizing new technologies such as fault-tolerant quantum computation [4]. By far the most widely studied system within the field of TI research is Bi 2 T 3 (T=Se,Te) [5][6][7][8][9][10]. To date, the major experimental efforts on these noninteracting bismuth-based TI materials have focused on refining measurement techniques in order to detect signatures of surface states.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Distinguished from ordinary insulators by the so-called Z 2 topological invariants associated with the bulk electronic band structure [2,3], this class of materials is characterized by nonlocal topology of the electronic structure that gives rise to new electronic states with promise for realizing new technologies such as fault-tolerant quantum computation [4]. By far the most widely studied system within the field of TI research is Bi 2 T 3 (T=Se,Te) [5][6][7][8][9][10]. To date, the major experimental efforts on these noninteracting bismuth-based TI materials have focused on refining measurement techniques in order to detect signatures of surface states.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Recently, Rashba induced charge-spin interconversions, with a higher efficiency than that from SHE, have been detected in Bi/Ag, α-Sn/Ag [7][8][9][10], LaAlO3/SrTiO3 [11]. On the other hand, the topological surface states (TSS) of topological insulators (TIs) are another interfacial mechanism for achieving efficient charge-to-spin conversion due to the strong spin orbit coupling (SOC) and inherent spinmomentum locking, despite of the inevitable bulk transport [3,4,[12][13][14][15][16][17]. Therefore, understanding and optimization of the interfacial effects is of significance and great interest for efficient spincurrent generation in SOT based spintronics devices.…”
mentioning
confidence: 99%
“…Topological insulators are a state of quantum matter [11][12][13], in which the surface is metallic, while the interior is insulating. Spin-electricity conversion on TI materials has recently been investigated using spin pumping for bulk-metallic samples (Bi 2 Se 3 ) [14][15][16] and also for bulk-insulating ones [17]. In a previous report [17], some authors of the present paper demonstrated the spinelectricity conversion induced by spin pumping into surface states of TIs, Bi 1.5 Sb 0.5 Te 1.7 Se 1.3 (BSTS) [18,19] and Sn-doped Bi 2 Te 2 Se (SnBTS) [20] in contact with Py.…”
mentioning
confidence: 99%